Pengaruh Motivasi Keluarga dan Pembelajaran Kewirausahaan Terhadap Minat Berwirausaha Siswa SMA Negeri 1 Gangga - Putri Ambar Wati; Ika Yuliana (Indo Publishing, 2025)
Unemployment becomes Indonesia's main economic challenge requiring alternative solutions through entrepreneurial spirit development among young generation. This study aims to analyze the influence of family motivation and entrepreneurship education on entrepreneurial interest of students at SMA Negeri 1 Gangga. The research method used quantitative approach with causal design on 55 students of class XII business major as respondents through census technique. Data were collected using Likert scale questionnaires and analyzed using multiple linear regression. Results showed family motivation has significant positive effect on entrepreneurial interest with regression coefficient 0.267 and significance 0.049. Entrepreneurship education also has significant positive effect with coefficient 0.220 and significance 0.013. Simultaneous effect of both variables shows F-value 251.332 with significance 0.003 and determination coefficient 75%. The study concludes that combination of family motivation and entrepreneurship education creates optimal synergy in fostering students' entrepreneurial interest, providing empirical foundation for developing entrepreneurship programs involving families as active stakeholders in addressing unemployment challenges.